Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.
Trending News
Simplify the following...?
i^2
i^78
(7+8i)(7-8i)
5 Answers
- Cool InfernoLv 61 decade agoFavorite Answer
1) -1
2) -1
3) 113
Hope i helped! ;P
P.S. the guy below me is wrong when saying i to an even number is -1
the rule is:
i to an even number divisible by 2 but not by 4 is -1
i to an even number not divisible by 2 but divisible by 4 is -1
This is because i^2 = -1
and
i^4 = i^2 x i^2 = -1 x -1 = 1
Hope this helped more! ;P
- 1 decade ago
We know that i=sqrt(-1)
so i^2= (sqrt(-1))^2
= -1
The next part is where we have to come up with a pattern. Rather than multiplying 78 times, we can conclude the following.
We know
i = i
i^2= -1
i^3=-i (i^2 times i)
i^4=1 (i^2 times i^2, -1x-1=1)
i^5=i (i^4 times i)
If we kept going we can definitely see a repeating cycle, every 4 powers it starts over. So now lets take the power of I, and divide by 4 (with remainder). 78/4= 19 R 2.
The only thing we really care about is the remainder. Basically what we just did was find out how many 1's we have (the whole number, so 1^19=1). This is shown exponentially
(i^4)^19 = 1^19 = 1
Now that we have gotten rid of the i^4 we are left with i^2. i^2=-1.
1x -1= -1
i^78=-1
Third.
Treat this like a quadratic and use the FOIL method to simplify.
49-56i +56i - 64i^2
49 - (-64)
49+64=113
Another thing to do here is notice that these are conjugates (a-bi)(a+bi) so you will just get a^2 +b^2.
- 1 decade ago
1) i^2 = -1 (by definition)
2) i^4 = 1 so write 78 = 19*4 + 2, then i^78 = i^(19*4 + 2) = i^(19*4)*i^2 = (i^4)^19 * i^2 = 1^19 * (-1) = -1
3) (7+8i)(7-8i) = 7^2 - (8i)^2 = 49 - 64*i^2 = 49+64 = 113
- Anonymous1 decade ago
i is the square root of -1, so i^2 = -1.
i to an even number is -1. so i^78 = -1.
(7+8i)(7-8i) = 7^2 - (8i)^2
= 49 - 64(-1)
= 49 + 64
= 113
- How do you think about the answers? You can sign in to vote the answer.
- cidyahLv 71 decade ago
i^2=-1
i^4= (i^2)(i^2)=1
i^6=i^4(i^2)=-1
i^8=i^6 i^2=1
i^78 = 78 is a multiple of 3, so it is -1